2011
DOI: 10.1007/s12288-011-0066-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lymphoblastic Leukaemia with Microfilaria: A Rare Coincidence in Bone Marrow Aspirate

Abstract: Microfilariae in bone marrow aspirates have been reported occasionally, but until now no case has been reported in association with acute leukaemia. This is a unique finding, not mentioned in literature. Microfilariae are seen mainly in peripheral blood smears (PBS) and rarely in bone marrow aspirate, but this surprisingly did not show any parasite in PBS. Meticulous examination of bone marrow smears revealed acute lymphoblastic leukaemia and a few interspersed microfilariae. This rare combination, reported fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Uzma Zafar et al (8) reported an interesting case of low back pain and destruction of first lumbar vertebra by the microfilariae residing in the bone marrow. There were several case reports of huge splenomegaly in leukaemia patients with incidental detection of bone marrow microfilariae (9)(10)(11). Possible explanation for splenomegaly in those cases were due to leukaemia not filariasis because spleen is usually not involved in filariasis except in some experimentally infected animals although Schuurkamp GJ et al (14) showed occurrence of filarial splenomegaly in their articles.…”
Section: Discussionmentioning
confidence: 99%
“…Uzma Zafar et al (8) reported an interesting case of low back pain and destruction of first lumbar vertebra by the microfilariae residing in the bone marrow. There were several case reports of huge splenomegaly in leukaemia patients with incidental detection of bone marrow microfilariae (9)(10)(11). Possible explanation for splenomegaly in those cases were due to leukaemia not filariasis because spleen is usually not involved in filariasis except in some experimentally infected animals although Schuurkamp GJ et al (14) showed occurrence of filarial splenomegaly in their articles.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that in cases of bone marrow microfilaria, the above mentioned classical clinical presentation is often lacking [5][6][7][8][9][10][11][12]. Similarly our case also lacked the classical clinical presentation.…”
Section: Discussionmentioning
confidence: 56%
“…It is also possible that they may get trapped in the bone marrow during their circulation in the peripheral blood. Including the present case, none of the published cases where microfilaria was found in the bone marrow aspirates, had a classical clinical presentation of lymphatic filariasis (5)(6)(7)(8)(9)(10)(11). A diagnosis of filariasis was made after demonstrating the microfilariae in the bone marrow aspirate or in the peripheral blood smears.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 80%